(untitled) (Communications in Mathematical Research, 2020)
Let A be a Frobenius k-algebra. The matrix algebra R=pmatrixA & _AA_k [1mm]_kA_A & kpmatrix is called a generalized matrix algebra over a Frobenius algebra A. In this paper we show that R is also a Frobenius algebra.